2014
DOI: 10.7603/s40706-013-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient e-Marketing in Tourism through a Novel Customer Relationship Management Model

Abstract: This paper proposes an efficient customer relationship management model based on technological convergence of emerging next generation networks, such as interactive digital television and network multimedia systems. The proposed research approach is exploited in tourism sector for effective destination management, enabling for personalized e-marketing strategies and facilitating marketers to accomplish optimum marketing data analysis. The proposed research approach is evaluated for its applicability and useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
0
2
5
Order By: Relevance
“…Based on the results of data analysis using SmartPLS obtained p value 0.149> 0.050 so it can be concluded that Customer Oriented has no significant effect on Business Performance through Customer Loyalty, an increase in the Customer Oriented variable will have an insignificant effect on increasing the Business Performance variable and a decrease in the Customer Oriented variable will have an effect not significant to the decrease in the Business Performance variable through Customer Loyalty. This result is not in line with the research conducted by Tsiotsou et al (2011);Trihas et al (2013) that Customer Oriented has a positive and significant effect on Business Performance through Customer Loyalty…”
Section: Relationship Between E-marketing and Business Performance Th...contrasting
confidence: 93%
See 4 more Smart Citations
“…Based on the results of data analysis using SmartPLS obtained p value 0.149> 0.050 so it can be concluded that Customer Oriented has no significant effect on Business Performance through Customer Loyalty, an increase in the Customer Oriented variable will have an insignificant effect on increasing the Business Performance variable and a decrease in the Customer Oriented variable will have an effect not significant to the decrease in the Business Performance variable through Customer Loyalty. This result is not in line with the research conducted by Tsiotsou et al (2011);Trihas et al (2013) that Customer Oriented has a positive and significant effect on Business Performance through Customer Loyalty…”
Section: Relationship Between E-marketing and Business Performance Th...contrasting
confidence: 93%
“…Based on the results of data analysis using SmartPLS obtained p value 0.393 > 0.050 so it is concluded that e-marketing has no significant effect on Customer Loyalty, an increase in emarketing variable will have an insignificant effect on increasing customer loyalty variables and decreasing e-marketing variables will have an effect not significant to the decrease in customer loyalty variable. This result is not in line with the research conducted by Sheikh et al (2018); Tsiotsou et al (2011);Trihas et al ( 2013) that emarketing has a positive and significant effect on Customer Loyalty.…”
Section: Relationship Between E-marketing and Customer Loyaltycontrasting
confidence: 79%
See 3 more Smart Citations